Consumption‐Based Fixed Rates: Harmonizing Water Conservation and Revenue Stability. Issue 3 (1st March 2015) - Spang, Edward S.; Miller, Sara; Williams, Matt; Loge, Frank J.
Abstract : Water utilities struggle with the need to promote water conservation while maintaining financial solvency—a common challenge referred to as the "new normal." However, under typical cost and revenue structures, water utilities experience significant revenue shortfalls when water use lags behind projected customer consumption (either by conservation or other factors). Subsequently, water providers are obligated to raise rates more frequently and/or more dramatically than originally anticipated. This problem arises primarily when the fixed and variable portions of utility costs are not aligned with the fixed and variable portions of revenue. This article presents a new water‐pricing mechanism—consumption‐based fixed rates—that harmonizes costs and revenues yet still promotes conservation through the innovative inclusion of volumetric fixed charges. As such, consumption‐based fixed rates represent a potentially useful solution for water utilities to effectively balance conservation and revenue stability in an equitable and sustainable manner.